ANALISIS MINAT BACA ANGGOTA MASYARAKAT DI RUMAH BACA TAMAN ALUN KAPUAS PONTIANAK - Karisma, Karisma; Rustiyarso, Rustiyarso; Hidayah, Riama Al (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbsractThis study aims to determine the reading interest of community members at the Taman Alun Kapuas Pontianak Reading House. The research approach with desriptive methods. Data collection techniques used were observation guides, interview guides, and notebooks along with archives. Data analysis techniques used in data reduction, data presentation, and drawing conclusions. The analysisin the study was presented descriptive using as many as 5 informants consisting of two reading house officers namely Mrs. N and Mrs. DI, as well as three visitors of the reading house namely Mrs. M, sister FW, and sister SM. The results of this study indicate that the frequency of visits to borrower transaction readings is still relative low, namely visitors only visit onceÂ  a week on holidays, saturdat and Sunday, reading duration of visitors is also still short, only about 60 minutes and it is also interspersed with playing cellphones and catthing, and the destination from visitors coming to the reading house is to fill in the free time and get entertainment.Â Keyword: Community Members, Reading House, Reading Interest